Audio-post Company Communication Strategy in Jakarta on Maintaining Client Loyalty in Television Advertising - Zalfa Qathrunnada; Catur Nugroho (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
The visual package of an advertisement on television will not be communicated perfectly to the audience if it’s not supported by good audio quality and those who have a role in making audio in television advertisements are audio-post companies. Advertising spending in Indonesia continues to increase every year by seven percent and dominated by television commercial with a total of 79.2 percent. Based on this, more and more audio-post companies are emerging now that produce audio for television commercial in Jakarta and certainly makes competition in this industry more obvious. But even so, they still have their loyal clients that have stayed from the past until now. One of these audio-post companies is Cut2Cut studio, which was founded in 2002 and has loyal clients from well-known brands. Therefore, this study aims to find out how Cut2Cut studio's communication strategy maintains client loyalty to television commercial. The method used is qualitative with a case study approach. The results of the study state that Cut2Cut studio carries out several strategic stages including formulating strategies that focus on approaching clients, implementing strategies by maintaining communication with clients as well as providing special treatment, as well as evaluating strategies by conducting routine evaluations based on obstacles that need to be discussed